Accelerated ageing test and durability prediction model for mechanical properties of GFRP connectors in precast concrete sandwich panels. (20th March 2020) - Xue, Weichen; Li, Ya; Fu, Kai; Hu, Xiang; Li, Yan
Highlights: Durability of GFRP connectors in alkaline solution at elevated temperatures was tested. SEM micrographs confirmed degradation in fibre/matrix interfacial bonding after conditioning. Ageing conditions degraded tensile and compressive properties of GFRP connectors. A prediction model for tensile and compressive strength of GFRP connectors was proposed based on Arrhenius equation. Abstract: Glass fiber-reinforced polymer (GFRP) connectors are the key components in precast concrete sandwich panels, because they not only provide continuity between two concrete wythes but also promote thermal efficiency of the panels. This paper presents an experimental study on durability of GFRP connectors in alkaline solution (simulated concrete environment) with variable parameters of temperature (40, 60, and 80 °C) and conditioning time (3.65, 18, 36.5, 92 and 183 days). A total of 160 specimens were immersed in the alkaline solution with a composition specified in ACI 440.3R-12 at elevated temperatures. Scanning electron microscope (SEM) was used to observe the degradation mechanism of the specimens, and the phenomenon of debonding between fibers and resin could be observed more obvious with the increase of erosion time and temperature. The test results also showed that, after 183 days of immersion at 60 °C, tensile strength and modulus of elasticity of the specimens decreased about 38.85% and 21.45% respectively, while compressive strength and modulus of elasticity of the specimens decreased about 40.18% and 27.62%. Finally, a prediction model of tensile and compressive strength after conditioning over time at varied temperatures was proposed based on Arrhenius equation.